Dose‐ and time‐dependent effects of an immune challenge on fish across biological levels. Issue 2 (17th November 2020) - Petitjean, Quentin; Jacquin, Lisa; LeHénaff, Michel; Perrault, Annie; Cousseau, Myriam; Laffaille, Pascal; Jean, Séverine
Abstract: Due to global changes, fish are increasingly exposed to immune challenges associated with disease outbreaks in aquatic ecosystems. Adjustments in physiology and behavior are generally critical to maintaining homeostasis after an immune challenge, but there is limited knowledge on the specific thresholds and dynamics of responses across levels of biological organization in fish. In this study, we tested how different concentrations of an antigens mixture (phytohemagglutinin and lipopolysaccharide) affected innate immunity with potential consequences on oxidative stress, energy reserves, body condition, and behavior across time, using the common gudgeon ( Gobio sp.) as model species. The immune challenge induced a transitory increase in lytic enzyme activity (i.e., lysozyme) and local immune response (i.e., skin swelling) 2 days after the antigen injection. The available energy stored in muscle was also reduced 4 days after injection, without inducing oxidative stress at the cellular level. Overall, the immune challenge induced limited costs at the molecular and cellular levels but had strong effects at the whole organism level, especially on behavior. Indeed, fish swimming activity and sociability were affected in a dose‐ and time‐dependent manner. These results suggest that immune challenges have dose‐dependent effects across levels of biological organization and that behavior is a key response trait to cope with pathogen‐induced immune costs in the wild, although fitness consequences remain to be tested. Abstract : Here, we tested how different concentrations of an antigens mixture affected fish innate immunity with potential consequences on oxidative stress, energy reserves, body condition, and behavior across time. We found that the effects of immune challenges were dose‐ and time‐dependent. Immune challenges at medium and high doses induced limited energy and oxidative costs, but strongly inhibited swimming activity and sociability after 4 days, suggesting that behavior is a key response trait to cope with immune costs in wild fish. Highlights: The costs induced by immune challenge vary in fish in a dose‐ and time‐dependent manner. Medium and high doses of antigens mostly affected immune and behavioral traits with limited effects on fish condition, likely due to energy reallocation.